Preliminary assessment on the growth performance of Dryobalanops beccarii Dyer planted under enrichment planting technique at Gunung Apeng Forest Reserve, Sarawak, Malaysia - Mohd Effendi, Wasli; Hamsawi, Sani; Ho, Soo Ying; Mugunthan, P.; Aisyah, Zainudin Zatil; Jonathan, Lat; Lee, Pick Sean (Graduate School of Kuroshio Science, Kochi University, 2014)
Reforestation of degraded areas in Sarawak, Malaysia is vital in an effort to conserve the dynamic forest resources in Borneo. A preliminary assessment was conducted in providing the information on the growth performance and survival rate of planted indigenous Dipterocarp species (Dryobalanops beccarii Dyer) for reforestation purpose in Sarawak. In this study, reforestation areas which were planted with Dryobalanops beccarii under line planting technique were selected. Study sites were established in the reforestation areas (areas planted with D. beccarii in the year 2005; DB05 and 2008; DB08). The assessment on the growth performance of planted D. beccarii at different age stand was evaluated by measuring the stem diameter, height and survival rate from October 2010 to December 2012. Our findings showed that the survival rate of planted trees in DB05 and DB08 were at 88% and 86%, respectively. For the tree height and stem diameter, the results showed that the tree height and stem diameter in DB05 was 4.9 m and 3.6 cm, respectively. Meanwhile, the assessment on the tree height and stem diameter in DB08 was 1.9 m and 0.9 cm, respectively. The mean annual increment in height (MAIH) and diameter (MAID) of planted D. beccarii in DB05 was significantly higher than DB08. High survival rate and substantial growth performance of D. beccarii indicated that site edaphic condition such as competition between planted and existing pioneer species of the study area may have affected the survival rate and growth performance of planted D. beccarii. Therefore, further studies are required in order to find out the soil-plant relationship of D. beccarii as well as other edaphic factors which may affect the growth and survival of D. beccarii under line planting technique.